Evaluation of Gas Flare Recovery System Selection Using the Ahp Method to Increase Gas Sales Potential at PT Xyz's Oil and Gas Fields - Sabdo Waluyo; Ruri Agung Wahyuono (Journal of Social Research, 2026)
Flare gas utilization has become an important issue in the oil and gas industry due to its economic potential and contribution to greenhouse gas emissions. Continuous gas flaring not only results in energy losses but also limits opportunities to increase gas sales potential. Therefore, selecting an appropriate Flare Gas Recovery (FGR) technology is essential to support operational efficiency and emission reduction targets, including the Zero Routine Flaring by 2030 initiative. This study aims to evaluate and determine the most suitable FGR technology alternative for PT XYZ’s oil and gas field by applying a systematic multi-criteria decision-making approach. The research employed the Analytic Hierarchy Process (AHP) method to evaluate three FGR alternatives: LPG extraction, High-Pressure (HP) fuel gas recovery, and recycle compression. The evaluation criteria included cost, implementation time, operability, recovered condensate potential, and manpower requirements. Data were collected through expert interviews, technical document analysis, operational data review, and process simulation evaluation. The results showed that recycle compression (T3) achieved the highest priority based on the AHP calculation, with a final priority value of 0.4070, followed by LPG recovery (T1) with a value of 0.3315 and HP fuel gas recovery (T2) with a value of 0.2615. Sensitivity analysis confirmed that T3 provided the most stable decision under various changes in evaluation criteria. This study concludes that the AHP-based evaluation model can support objective technology selection and provide a practical framework for improving gas utilization, reducing flaring emissions, and enhancing operational efficiency in upstream oil and gas facilities.